Implementation of The Independent Learning Curriculum in Kindergarten - Arum, Rezki Perwita; Putro, Khamim Zarkasih; Jatmiko, Agus (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2023)
This research focuses on the independent curriculum applied in Karana Jaya Kindergarten, Jati Agung District, South Lampung. The independent curriculum impacts the implementation of education in Karana Jaya Kindergarten. Karana Jaya Kindergarten is very important in providing healthy and optimal child growth and development facilities following the community's values, norms, and expectations. This research uses qualitative methods with a descriptive approach. Data is collected through documentaries, literature studies, observations, and surveys. The subjects of this study were 40 children and six teachers. The results showed how Karana Jaya Kindergarten implements an independent curriculum by providing various interesting experiences and activities that stimulate the growth and development of children. Therefore, an environment that supports the growth and development of children is needed. The play-based learning paradigm that encourages independent learning has been successfully implemented.